'N-Angle': Clinical Indicator for Predictable Insertion of Ramal Bone Screws. Issue 4 (October 2021) - Patni, Vivek J; Kolge, Neeraj E; Pednekar, Madhura J
Introduction: The primary concern in the placement of ramal bone screws is the blind nature of the procedure, as there is a thick, mobile layer of soft tissue over the bone; also, the ramus is not a uniplanar structure but is swerving like a propeller blade. The purpose of this study was to evaluate the possibility of establishing clinical guidelines based on visible dental and soft-tissue landmarks for safe, reliable, and accurate insertion of ramal bone screws. Aims and Objectives: Our primary objective was to evaluate the angle formed between the appropriate direction of ramal-implant placement and the line tangential to the buccal surfaces of the first and second permanent molars. Our secondary objective was to evaluate the average distance of the neurovascular bundle from the tip of the bone screw. Materials and Methods: We obtained 80 cone beam computed tomography (CBCT) samples, marked reference lines and points on selected axial and coronal sections, and evaluated the following parameters using the software's linear- and angular-measurement device: the angle between the appropriate direction of ramal bone screw placement and the line tangential to the buccal surfaces of the first and second permanent molars; and the proximity of the bone screw to the neurovascular bundle. Results: The angle between the constructed line of insertion and the occlusal line, as evaluated from our study, was 19.04 (SD ± 6.89) degrees. The proximity of the neurovascular bundle from the screw is 7.1773 (SD ± 1.73988) mm. Conclusion: We can conclude that ramal bone screws can be placed with a comfortable margin of safety.